The Occipital Condyle Fracture in Pediatric Ages: (Case Report) - Arici, Lutfu; Kilinc, Ahmet; Ucler, Necati; Kaplan, Metin (Emergency Medicine Physicians Assoc Turkey, 2009)
Blunt traumas with high energy carry high risk for the occipital condyle fractures. 13-old-year girl was evaluated in emergency after the motor vehicle accident. The patient examination for the upper cervical pain in palpation. Cervical direct plain radiography was reported normal and the patient was immobilized with philedelphia cervical coller. After 3 days trauma the patient was examined again for the restricted in cervical lateral rotations and pain in Orthopedics clinic. The fracture type of our case was detected as Anderson and Montesano Type II occipital condyle fracture in 3-Dimensional cervical Computed Tomography. The management was carried out with philedalphia cervical coller immobilization. Occipital condyle fractures are very rare in pediatric ages. The diagnosis is difficult with cervical radiography. Occipital condyle fractures are considered in differential diagnosis of patients with localized upper cervical region pain, and sensitivity, restricted cervical activity. In these cases, cervical vertebras should be scaned with Computed Tomography.
Keywords: Pediatric cervical trauma; Occipital condyle fracture; 3D computed tomography